2001
DOI: 10.1093/ps/80.7.906
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biogenic Amines on Growth and The Incidence of Proventricular Lesions in Broiler Chickens

Abstract: Biogenic amines have been implicated in a malabsorption syndrome characterized by decreases in feed efficiency and enlargement of the proventriculus. Two studies were conducted to determine the effects of two common biogenic amines, histamine (HIS) and cadaverine (CAD), on broiler growth and the incidence of pathologies associated with proventriculitis. In the first experiment, broiler chicks were fed diets containing 0, 0.01, 0.05, 0.1, and 0.2% HIS, and in the second experiment chicks were fed diets containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…It has been shown that biogenic amines are involved in the occurrence of malabsorption syndrome, which is characterized by decreased feed efficiency and enlargement of the proventriculus (Stuart et al, 1986). Barnes et al (2001) demonstrated that dietary histidine and cadaverine can cause the pathologies associated with proventriculitis. The action of histidine and cadaverine appeared to be additive or synergistic.…”
Section: Infectious Agentsmentioning
confidence: 99%
“…It has been shown that biogenic amines are involved in the occurrence of malabsorption syndrome, which is characterized by decreased feed efficiency and enlargement of the proventriculus (Stuart et al, 1986). Barnes et al (2001) demonstrated that dietary histidine and cadaverine can cause the pathologies associated with proventriculitis. The action of histidine and cadaverine appeared to be additive or synergistic.…”
Section: Infectious Agentsmentioning
confidence: 99%
“…Histamine at 0.2%, or the combination of 0.1% histamine and 0.1% cadaverine, increased the circumference of the gastric isthmus by 14 and 16%, respectively, and the relative weight of the proventriculus by 21 and 36%, respectively. Histamine and cadaverine increased the total number, incidence, and severity of gizzard erosion, produced proventricular ulcers, and decreased the prominence of gastric papillae (Barnes et al ., 2001).…”
Section: Transmissible Proventriculitis In Broilers 89mentioning
confidence: 99%
“…They may be infectious or dietary agents. These include reovirus (Kouwenhoven et al ., 1978;Page et al ., 1982;Apple, 1988;Songserm et al ., 2002;Opengart, 2003), IBDV (Bayyari et al ., 1995a;Wilson et al ., 1995;Newberry, 1996;Skeeles & Newberry, 2000;Skeeles et al ., 1998;Huff et al ., 2001;Pantin-Jackwood & Brown, 2003;Dormitorio, 2004), adenovirus (Kouwenhoven et al ., 1978;Lenz et al ., 1998;Guy et al ., 2006), infectious bronchitis virus (IBV) (JiYong, 2000;XieZheng et al ., 2000;Yu et al ., 2001), clostridium (Huff et al ., 2001;Schulze & Heidrick, 2001), biogenic amines (Huff et al ., 1994;Barnes et al ., 2001), copper sulphate (Bayyari et al ., 1995b;Fisher et al ., 1973;Jensen, & Maurice, 1978;Wideman et al ., 1995), and mycotoxins (Domer et al ., 1983). However, none of these agents has been conclusively proved to cause TP.…”
Section: Introductionmentioning
confidence: 99%
“…Biogenic amines have been found in many animal by-product meals (Poole 1993; Barnes et al 2001) and food matrices including fish (Veciana-Nogues et al 1995), cheese (Moret et al 1992), wine (Ibe et al 1991), beer (Kalac et al 1997), processed meat (Eerola et al 1993), chocolate (Baker et al 1987) and fruit (Morilla et al 1996).…”
Section: Introductionmentioning
confidence: 99%